Multiple intelligences of educational administrators, their performance, and administrative career match - Carlos, Judy Lee (2008)
This study examined the MI profile to identify which intelligences are commonly strong in top-performing educational administrators, as evidenced by the high scholastic ranking among the local secondary schools. Questionnaires regarding the views of the administrators on MI were handed out to 31 educational administrators of the top secondary schools in Metro Manila based on the result of the most recent NCAE. Their self-assessment of their MI profile were validated by their subordinates, and their superiors, thus comprising the 99 respondents in the study. The study validated Howard Gardner's idea that if one is high in interpersonal and/or intrapersonal intelligence, one of the careers that would best fit that person is in administration. This implies that during a teacher's promotion to the administrative level, of the nine intelligences, interpersonal and intrapersonal intelligences are critical and should be scrutinized among administrative candidates and strengthened in incumbents.
Thesis (M.A. Educational Administration)--University of the Philippines, Diliman.
Keywords: Multiple intelligences; School administrators -- Philippines -- Manila Metropolitan Area; School superintendents and principals -- Philippines -- Manila Metropolitan Area; School management and organization -- Philippines -- Manila Metropolitan Area